2020
DOI: 10.1136/emermed-2019-209389
|View full text |Cite
|
Sign up to set email alerts
|

I-FiBH trial: intravenous fluids in benign headaches—a randomised, single-blinded clinical trial

Abstract: BackgroundMany emergency physicians use an intravenous fluid bolus as part of a ‘cocktail’ of therapies for patients with headache, but it is unclear if this is beneficial. The objective of this study was to determine if an intravenous fluid bolus helps reduce pain or improve other outcomes in patients who present to the ED with a benign headache.MethodsThis was a randomised, single-blinded, clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…IV fluids are often given as a routine part of migraine therapy in emergency settings [31]. Recently published studies have indicated that IV fluids offer no benefit in treating migraine headache pain [37,38]. The results of our study support this lack of benefit, as IV fluid boluses were associated with increased need for second round medications.…”
Section: Previous Literaturesupporting
confidence: 73%
“…IV fluids are often given as a routine part of migraine therapy in emergency settings [31]. Recently published studies have indicated that IV fluids offer no benefit in treating migraine headache pain [37,38]. The results of our study support this lack of benefit, as IV fluid boluses were associated with increased need for second round medications.…”
Section: Previous Literaturesupporting
confidence: 73%
“…Richer et al reported that IV infusion of normal saline (10 ml/kg) over 30 min resulted in a pain reduction of 12.5 mm VAS; the reduction was deemed not meaningful 31 . Other studies demonstrated that the addition of IV fluid (up to 1 L of normal saline) to IV neuroleptic accomplished no more pain control than IV neuroleptics alone 32–34 . Although there is no consensus on the role of hydration in migraine treatment, IV fluid is commonly used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…31 Other studies demonstrated that the addition of IV fluid (up to 1 L of normal saline) to IV neuroleptic accomplished no more pain control than IV neuroleptics alone. [32][33][34] Although there is no consensus on the role of hydration in migraine treatment, IV fluid is commonly used in clinical practice. In addition, previous studies of IV ketorolac on renal colic or postoperative pain have used a smaller volume (50 ml) or IV push.…”
Section: Discussionmentioning
confidence: 99%